Two new 2, 5-diketopiperazine derivatives from mangrove-derived endophytic fungus Nigrospora camelliae-sinensis S30. Issue 14 (15th July 2022) - Huang, Dan-Yu; Nong, Xu-Hua; Zhang, Yu-Qin; Xu, Wei; Sun, Long-Yu; Zhang, Tao; Chen, Guang-Ying; Han, Chang-Ri
Abstract: Two new 2, 5-diketopiperazines derivatives (1-2 ), together with eight known analogs (3-10 ), were isolated from a culture broth of an endophytic fungus Nigrospora camelliae-sinensis S30, derived from mangrove Lumnitzera littorea . Their complete structures were determined by a detailed analysis of spectroscopic data and ECD calculations. The antimicrobial activity and neuroprotective activity of these isolated compounds were also evaluated. Graphical Abstract: UF0001